Analisis Framing Representasi Maskulinitas dalam Film Guru Bangsa Tjokroaminoto - Siti Asiyah; M. Ibrohim Al-Bajuri (IQTIDA : Journal of Da'wah and Communication, 2022)
A biographical film is a film that tells the life story of the character. There are many messages and values contained in biographical films, because they are taken from true stories. One of them is the film Guru Bangsa Tjokroaminoto. This film tells the journey of a fighter and pioneer of Indonesian independence, Haji Oemar Said Tjokroaminoto. The focus of this study is to find out the representation of masculinity from HOS Tjokroaminoto and how the impact of this masculine trait on film audiences, masculinity is the social role, behavior and meaning assigned to men. The masculinity indicators are taken from Deborah David & Robert Brannon's theory of masculinity, namely No Sissy Stuff, Be a Big Wheel, Be a Sturdy Oak, Give em Hell. This study uses a qualitative research method, while to examine the film using theAnalysis approach Framing from Zong dang Pan & Gerald M. Kosicki. The results showed that HOS Tjokroaminoto represented the masculinity of Be a Big Wheel, Be a Sturdy Oak, Give em Hell. However, the researcher did not find that HOS Tjokroaminoto represents the masculinity of No Sissy Stuff, because in his daily life he uses jarit cloth, while the jarit itself is identical to the cloth worn by women. The impact of HOS Tjokroaminoto's masculinity on film audiences is that some of the characteristics of HOS Tjokroaminoto's masculinity should be imitated by the current generation.